A method for preparing a metal oxide film and a high-performance perovskite solar cell
Preparing high-quality metal oxide films as electron transport layers by rapid heat treatment method, solving the photocatalysis problem of oxide transport layer in perovskite solar cells, improving the photoelectric performance and stability of the device, and achieving efficient large-area preparation .
Patent Information
- Application Number
- CN202210931656.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-04
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-08-04
AI Technical Summary
In perovskite solar cells, the high light transmittance of the oxide transport layer leads to photocatalysis, resulting in decomposition of the perovskite active layer, affecting device performance and stability. The existing preparation methods are affected by the environment and solution dispersion, making it difficult to Achieve large-area preparation.
A dense metal tin oxide or zinc oxide film is prepared as an electron transport layer by rapid heat treatment method, and a high-quality metal oxide film is formed by high-temperature oxidation and high-energy tungsten halogen lamp to improve crystallinity and light transmittance.
It effectively improves the photoelectric conversion efficiency and short-circuit current of perovskite solar cells, reduces the decomposition of perovskite film at the interface, improves the long-term stability of the device, and simplifies the large-area preparation process.
Smart Images

Figure CN115394656B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of perovskite photovoltaics, and specifically relates to a method for efficiently preparing an oxide transport layer and a method for preparing a high-performance perovskite solar cell. Background Art
[0002] In the preparation of perovskite solar cells, the quality of the electron transport layer is crucial for the preparation of efficient perovskite solar cells. Since the oxide is on the light-receiving surface, the higher the transmittance of the oxide, the more light the perovskite can absorb, and the corresponding photocurrent is higher. Under long-term use conditions, the oxide transport layer has photocatalytic properties under ultraviolet light, so that the perovskite active layer film decomposes at the interface with the transport layer, resulting in poor device performance; this also leads to poor long-term stability of the perovskite device, and in most cases, ultraviolet light needs to be filtered out by an ultraviolet filter. The crystallinity of the oxide directly affects its own stability. The higher the crystallinity, the stronger the ability to transmit electrons and the better the interface contact with the perovskite, which is beneficial to reduce the series resistance of the device. At present, the preparation of metal oxide transport layers mainly adopts oxide nanoparticle annealing to obtain oxide films. This method is greatly affected by the environment and the dispersibility of the solution, which is not conducive to storage and large-area preparation.
[0003] The effect of the photocatalytic activity of the electron transport layer on the quality of the perovskite film can be reduced by the interface passivation method. However, the interface passivation method does not take advantage of the large-scale production of perovskites; and in theory, the interface passivated material will bring unnecessary optical losses, and its passivation effect will gradually disappear over time, and it is impossible to fundamentally solve such problems. Therefore, controlling the quality of the oxide transport layer is crucial to improving the photoelectric performance of perovskite solar cells and the commercialization of perovskite cells. Summary of the invention
[0004] In view of the deficiencies of the prior art, the present invention aims to provide a method for preparing a metal oxide film and a high-performance perovskite solar cell.
[0005] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] The perovskite solar cell is a positive device structure, which includes from bottom to top: transparent conductive glass, tin dioxide electron transport layer, perovskite active layer, hole transport layer and electrode layer, wherein the tin dioxide electron transport layer is prepared by rapid thermal treatment method; the method specifically comprises the following steps:
[0007] (1) Treat the conductive glass substrate with UV-ozone for 10-20 minutes.
[0008] Further, the preparation method of the tin dioxide electron transport layer is as follows:
[0009] Solution method: Mix the tin dioxide nanocrystal solution with deionized water to form a uniform precursor solution, wherein the mass fraction of the tin dioxide nanocrystal solution is 15-20%. Spin the precursor solution on the transparent conductive glass at a speed of 2000-5000 rpm for 25-40 seconds, then preheat at 60-80°C for 5-10 minutes, and anneal at 130-200°C for 30-60 minutes to obtain a tin dioxide electron transport layer.
[0010] Rapid thermal treatment method: First, a metal tin or zinc film is prepared by thermally evaporating high-purity tin particles or zinc particles on a conductive glass substrate treated with UV ozone, and then transferred to a rapid thermal treatment furnace, and the temperature is rapidly raised to 300°C in an oxygen atmosphere and maintained for 10 minutes, and then annealed in a nitrogen atmosphere for 10 minutes, and finally slowly cooled to room temperature and taken out. A high-quality electron transport layer with excellent light transmittance is obtained.
[0011] (2) Preparation method of perovskite active layer:
[0012] The perovskite precursor solution is spin-coated or scraped onto a substrate, and a perovskite intermediate phase is formed on the substrate film by using an anti-solvent, blowing or vacuuming, and then the sample is heat-treated on a heating table at 100-170° C. for 10-60 minutes to obtain a precursor film. The precursor solution is formed by dissolving MAI, MABr, FAI, MACl and PbI2 powders and additives in a mixed solvent in a molar ratio, and the total molar concentration is 1.2-2 mol / L.
[0013] The hole transport layer is spiro-OMeTAD, and the preparation method thereof is as follows: drop a spiro-OMeTAD mixed solution on the surface of the perovskite film, and spin-coat at a speed of 3000-5000 rpm for 25-35 seconds;
[0014] The electrode layer is 100-150nm gold electrode or silver electrode
[0015] Furthermore, the transparent conductive glass (including the glass substrate and the transparent conductive electrode) is ITO or FTO transparent conductive glass, with a sheet resistance of 5 to 15Ω, a transmittance of 80 to 90%, a thickness of the conductive glass of 1 to 3 mm, and a thickness of the conductive electrode material of 150 to 300 nm.
[0016] Furthermore, the ambient humidity for preparing the perovskite active layer is ≤50%.
[0017] Furthermore, the hole transport layer is Spiro-OMeTAD, and the hole transport layer has a thickness of 100 to 200 nm.
[0018] Furthermore, the spiro-OMeTAD mixed solution is prepared by adding 72 mg spiro-OMeTAD, 17.5 uL acetonitrile solution of lithium bisimide with a concentration of 520 mg / mL, and 28.8 uL TBP into 1 mL chlorobenzene solvent.
[0019] Furthermore, the metal electrode layer material is gold or silver, and its thickness is 80-140 nm.
[0020] Compared with the prior art, the present invention has the following beneficial technical effects:
[0021] By means of a rapid thermal treatment method, the metal film is directly oxidized to form a dense tin oxide or zinc oxide film, and the obtained film is very uniform and conducive to large-area preparation. In a rapid thermal treatment furnace, the metal is melted into a liquid phase at a high temperature, which is conducive to full oxidation. On the other hand, a high-energy halogen tungsten lamp is used to break oxygen molecules into oxygen atoms, which is conducive to fully reacting with the metal in the liquid phase to form a dense metal oxide film, thereby improving the crystallization quality of the film. The metal oxide film is applied to perovskite solar cells, which can effectively improve the photoelectric conversion efficiency and short-circuit current of the device at the same time. The preparation process of using rapid thermal treatment to prepare a transmission layer to improve the photoelectric performance of perovskite solar cells is simple in the present invention, and has important practical value for preparing efficient and large-area perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The device structure of the perovskite solar cell in the embodiment of the present invention;
[0023] Figure 2 The transmission spectrum of the tin dioxide layer prepared by the solution method and the rapid thermal processing method in Example 1 of the present invention;
[0024] Figure 3 This is a scanning electron microscope image of a tin dioxide layer prepared by a rapid thermal treatment method in Example 1 of the present invention;
[0025] Figure 4 The XRD diagram of the tin dioxide film prepared by the solution method and the rapid thermal processing method in Example 1 of the present invention;
[0026] Figure 5 The external quantum efficiency diagram of the perovskite solar cell prepared by the tin dioxide layer prepared by the solution method and the rapid thermal processing method in Example 3 of the present invention;
[0027] Figure 6 The current-voltage curve of the perovskite solar cell prepared by the tin dioxide layer prepared by the solution method and the rapid thermal processing method in Example 3 of the present invention;
[0028] Figure 7The maximum output power stability curve of the perovskite solar cell prepared by the tin dioxide layer prepared by the solution method and the rapid thermal processing method in Example 3 of the present invention; DETAILED DESCRIPTION
[0029] The present invention provides a method for preparing a high-quality metal oxide film and a high-performance perovskite solar cell. The high-quality metal oxide film is prepared by a rapid thermal treatment method as an electron transport layer, which effectively reduces the decomposition of the perovskite film at the interface, thereby improving the long-term stability of the perovskite device. The method can effectively improve the photoelectric conversion efficiency and short-circuit current of the device at the same time. The present invention is further described in detail in conjunction with specific embodiments.
[0030] Example 1
[0031] 1. Cleaning ITO transparent conductive glass: Select ITO transparent conductive glass with a sheet resistance of 8-15Ω, a transmittance of 80-90%, and a thickness of 2mm, and ultrasonically clean it in deionized water, acetone, ethanol, and isopropanol solutions for 5 minutes, then blow it dry with nitrogen, and then use a UV ozone cleaning machine for 20 minutes.
[0032] 2. Preparation of tin dioxide film:
[0033] Rapid thermal processing method: First, thermal evaporation (evaporation rate is ) Prepare a 20-30nm metal tin film from high-purity tin particles, then transfer it to a rapid heat treatment furnace, quickly heat it to 400°C in 20s under an oxygen atmosphere and keep it for 10-15 minutes, finally slowly cool it to room temperature and take it out. A high-quality tin oxide film with excellent light transmittance is obtained, with a thickness of 20-30nm.
[0034] Solution method: Mix the tin dioxide nanocrystal solution with deionized water to form a uniform precursor solution, wherein the mass fraction of the tin dioxide nanocrystal solution is 15-20%. Spin the precursor solution on the transparent conductive glass at a speed of 2000-5000 rpm for 25-40 seconds, then preheat at 60-80°C for 5-10 minutes, and anneal at 130-200°C for 30-60 minutes to obtain a tin dioxide film with a thickness of 20-30 nm.
[0035] like Figure 2 The transmittance spectra of tin dioxide electron transport layers prepared by solution method and rapid thermal processing method show that in the 300-400nm band, the SnO2 film prepared by rapid thermal processing (SnO2-RTP) has a higher transmittance.
[0036] Figure 3This is a scanning electron microscope image of a tin oxide film prepared by rapid thermal treatment. The tin oxide film prepared by this method has large grains (particle size is about 100-200nm) and good density.
[0037] Figure 4 The XRD diagrams of tin dioxide films prepared by solution method and rapid thermal processing method. It can be seen from the figure that the peak intensity of the characteristic peaks of tin dioxide at around 30° and 52° is significantly improved, indicating that the SnO2 film prepared by rapid thermal processing (SnO2-RTP) has better crystallinity.
[0038] Example 2
[0039] 1. Cleaning the ITO transparent conductive glass: Same as Example 1.
[0040] 2. Preparation of zinc dioxide film:
[0041] Rapid thermal treatment method: First, a 20-30nm metal zinc film is prepared by magnetron sputtering high-purity zinc particles on a conductive glass substrate treated with UV ozone, and then transferred to a rapid thermal treatment furnace, and the temperature is rapidly raised to 400°C in 20s under an oxygen atmosphere and maintained for 10-15 minutes, and finally slowly cooled to room temperature and taken out. A high-quality zinc oxide film with excellent light transmittance is obtained, with a thickness of 20-30nm.
[0042] Example 3
[0043] In this example, the Figure 1 The positive device structure perovskite solar cell shown includes, from top to bottom and from bottom to top: ITO transparent conductive glass (including a glass substrate and an ITO transparent conductive electrode), a tin dioxide electron transport layer, a FAPbI3 perovskite active layer, a spiro-OMeTAD hole transport layer and an electrode layer.
[0044] 1. The method for cleaning the ITO transparent conductive glass and preparing the tin dioxide film as the electron transport layer is the same as that in Example 1.
[0045] 2. Preparation of perovskite layer: Spin or scrape the perovskite precursor solution on the substrate, use anti-solvent, blowing or vacuuming to make the substrate film form a perovskite intermediate phase, and then heat treat the sample on a heating table at 100-170°C for 10-60 minutes to obtain a precursor film. The precursor solution is formed by dissolving MAI, MABr, FAI, MACl and PbI2 powders and additives in a mixed solvent in a molar ratio, and the total molar concentration is 1.2-2 mol / L.
[0046] 3. Preparation of spiro-OMeTAD hole transport layer: drop the spiro-OMeTAD mixed solution on the surface of the perovskite film and spin coat it at 3000-5000 rpm for 25-35s; the spiro-OMeTAD mixed solution is prepared by adding 72 mg spiro-OMeTAD, 17.5 μL acetonitrile solution of lithium bisimide with a concentration of 520 mg / mL and 28.8 uL TBP into 1 mL chlorobenzene solvent to prepare the spiro-OMeTAD mixed solution.
[0047] 4. Preparation of electrode layer: Using thermal evaporation coating machine, at 2.0×10 -4 Under a vacuum condition of 1.3 Pa, 100 nm of gold was thermally evaporated onto the hole transport layer to form a metal electrode layer.
[0048] Figure 5 The external quantum efficiency diagram of perovskite solar cells prepared by tin dioxide layers prepared by solution method and rapid thermal treatment method. The tin dioxide film prepared by rapid thermal treatment has good density and crystallinity, which can effectively prevent leakage caused by direct contact between perovskite and transparent electrode. The prepared perovskite battery device has higher external quantum efficiency.
[0049] Table 1 shows the performance parameters of the battery of this embodiment and the control battery prepared by the solution method and the rapid thermal treatment method under the same experimental conditions. The IV curve is as follows: Figure 6 As shown, it can be seen that when the tin oxide film is prepared by the solution method, the short-circuit current and efficiency of the device are low, while the tin oxide film using rapid thermal treatment has good density and crystallinity, so that the short-circuit current and photoelectric conversion efficiency of the battery are improved. The preparation process of preparing the tin oxide film by rapid thermal treatment to improve the photoelectric performance of perovskite solar cells can be completed under ambient conditions, and the cost is low, and it is applicable to a variety of substrates, and has great potential for commercialization.
[0050] Table 1 Performance parameters of the battery in Example 1 and the control battery
[0051]
[0052] Figure 7 The maximum output power stability curves of the perovskite solar cells prepared with the tin dioxide layers prepared by the solution method and the rapid thermal treatment method in Example 3 of the present invention show that, compared with the electron transport layer prepared by the solution method, the high-quality metal oxide film prepared by the rapid thermal treatment method as the electron transport layer effectively reduces the decomposition of the perovskite film at the interface, thereby improving the long-term stability of the perovskite device.
[0053] The above is only a non-limiting implementation mode of the present invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the creative concept of the present invention and without making creative work. These all fall within the protection scope of the present invention.
Claims
1. A method for preparing a metal oxide film, characterized in that: Specifically: A metal element is grown on a substrate to form a metal film, wherein the metal element includes: tin and / or zinc, and the thickness of the metal film is 20-30nm; then the metal film is heat-treated and oxidized in a rapid thermal processing furnace to obtain a metal oxide film, wherein the thermal treatment conditions of the rapid thermal processing furnace are: rapidly heating to 400°C within 20s under an oxygen atmosphere, and maintaining at 400°C for 10-15 minutes.
2. The preparation method according to claim 1, characterized in that: The purity of the metal element is 99.99%.
3. The preparation method according to claim 1, characterized in that: The method of growing a metal element on a substrate to form a metal film is thermal evaporation, magnetron sputtering or electroplating.
4. A method for preparing a high-efficiency and high-stability perovskite layer solar cell, characterized in that: The device structures of the high-efficiency and high-stability perovskite solar cell are as follows from bottom to top: transparent conductive glass, electron transport layer, perovskite active layer, hole transport layer and metal electrode layer; The specific steps include: (1) Preparing a metal oxide film as an electron transport layer on a transparent conductive glass substrate using the method described in any one of claims 1 to 3; the metal oxide film is a tin oxide or zinc oxide film; (2) Preparing a perovskite active layer on the electron transport layer; (3) A hole transport layer and a metal electrode layer are sequentially prepared on the perovskite active layer to obtain a high-stability perovskite layer solar cell.
5. The preparation method according to claim 4, characterized in that: The perovskite active layer is a narrow bandgap perovskite film prepared by a two-step method, and has a thickness of 500-800 nm.
6. The preparation method according to claim 4, characterized in that: The perovskite active layer was prepared by the following method: Spin coating or scraping a PbI2 precursor solution on the electron transport layer, using a blowing or vacuuming method to form a PbI2 intermediate phase from the PbI2 precursor, then heat treating at 50-100° C. for 1-5 min to obtain a PbI2 film, spin coating or scraping a cationic solution on the PbI2 film after cooling, using a blowing or vacuuming method to form a perovskite intermediate phase, then heat treating at 100-170° C. for 10-60 min to obtain a precursor film; The cationic solution is formed by dissolving at least MAI, MABr, FAI and MACl powders in isopropanol in a molar ratio, and the total molar concentration is 0.6-1.0 mol / L.
7. The preparation method according to claim 4, characterized in that: The hole transport layer is Spiro-OMeTAD, and the hole transport layer has a thickness of 100-200 nm.
8. The preparation method according to claim 7, characterized in that: The Spiro-OMeTAD is Spiro-OMeTAD doped with TBP and lithium salt.
Citation Information
Patent Citations
Preparation method of metal hollow waveguide solar cell
CN104993061A
Preparation method of wide-band-gap perovskite active layer and solar cell
CN113594368A